2011
DOI: 10.1029/2011jc007023
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an artificial surfactant release on air‐sea gas fluxes during Deep Ocean Gas Exchange Experiment II

Abstract: [1] During the 2007 UK SOLAS Deep Ocean Gas Exchange Experiment in the northeast Atlantic Ocean, we conducted the first ever study of the effect of a deliberately released surfactant (oleyl alcohol) on gas transfer velocities (k w ) in the open ocean. Exchange rates were estimated with the 3 He/SF 6 dual tracer technique and from measured sea-to-air DMS fluxes and surface water concentrations. A total of seven k w estimates derived from 3 He/SF 6 were made, two of which were deemed to be influenced by the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
122
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(125 citation statements)
references
References 44 publications
3
122
0
Order By: Relevance
“…Hence, it is further hypothesized that a high concentration of chlorophyll in the water column can be taken as a direct indicator for pronounced, surfactantenriched microlayers (Asher, 1997) and nanolayers, leading to a decrease in gas exchange (see e.g. Duarte et al, 2009;Frew et al, 1990;Salter et al, 2011). A review of the current understanding of physicochemical aspects of the microlayer has been given recently by Cunliffe et al (2013).…”
Section: K Laß Et Al: Seasonal Signatures Of the Sea Surface Nanolayermentioning
confidence: 99%
“…Hence, it is further hypothesized that a high concentration of chlorophyll in the water column can be taken as a direct indicator for pronounced, surfactantenriched microlayers (Asher, 1997) and nanolayers, leading to a decrease in gas exchange (see e.g. Duarte et al, 2009;Frew et al, 1990;Salter et al, 2011). A review of the current understanding of physicochemical aspects of the microlayer has been given recently by Cunliffe et al (2013).…”
Section: K Laß Et Al: Seasonal Signatures Of the Sea Surface Nanolayermentioning
confidence: 99%
“…Whilst the Salter et al (2011) study has proven that surfactants can significantly impinge on gas transfer in the world's oceans, it is not yet clear that they do so at ambient levels. A recent study (Wurl et al 2011) found many of the world's oceans (subtropical, temperate and polar) are covered to a significant extent by surfactants.…”
Section: Surface Filmsmentioning
confidence: 99%
“…Support for this hypothesis came from Asher et al (1996) who demonstrated, in a series of laboratory experiments, that soluble surfactants inhibited gas transfer even under wave-breaking conditions. Very recently, Salter et al (2011) reported on a deliberate large scale release of an artificial surfactant (oleyl alcohol), in the north-east Atlantic Ocean. Gas transfer rates were measured by both the dual tracer technique (see Sect.…”
Section: Surface Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…*Corresponding author: Phone: +62-22-2511575, Fax:+62-22-2534107; Email: sony@sith.itb.ac.id (Salter et al 2011). This compound causes damage in hydrodynamics open water and cause CO exchange 2 effectivity that will harm the life at sea.…”
mentioning
confidence: 99%